The choice between two hypothesis tests - Erik Ruist (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Most standard hypothesis tests have high power only against a limited space of alternative hypotheses. With the advent of new tests for the same hypothesis, claimed to have higher power for some alternatives, but lower for other, the practitioner has to make a choice between alternative tests. This paper recommends the use of a pre-test to guide this choice, or the combined use of both tests.
Keywords: C12; 330; sign test; t test; two-dimensional criterion; Statistischer Test; Modell-Spezifikation; Statistische Methodenlehre